POTRET PERILAKU RELIGIUS MAHASISWA UIN SAYARIF HIDAYATULLAH JAKARTA - Ay Maryani (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2018)
This study describes the religious behavior of UIN Syarif Hidayatullah Jakarta students. The variables used are internal and external environment as independent variable and religious behavior as dependent variable. The internal environment variable consists of gender factor, (male and female). The external environmental variables comprise the faculty environment, the present resident and the place to grow. The present resident consist of dormitories, boarding houses and parents' homes and the place to grow consist of urban and rural environment. Religious behavior variables consist of habluminallah behavior and habluminannas behavior. Habluminallah's behavior measured by (1) knowledge of faith and worship, (2) attitudes toward faith and worship, and (3) practice of faith and worship. The habluminannas variable measured by (1) Islamic behavior for them self, like honest, discipline and good work / studyethics, trust and concern on legality, (2) Islamic behavior with others, like generous, cooperation, caring, respect to the people's rights and tolerance and (3) Islamic behavior for the natural surroundings, like love of nature and nature conservation efforts. The methodology used was (1) Statistical descriptive, (2) MANOVA (Multivariate Analysis of Variance) and (3) Independent sample t-test. The results showed the religious behavior UIN Syarif Hidayatullah Jakarta students has a very good category. This is indicated by the mean values for the behavior of haluminallah and habluminannas of 158.85 and 178.76, espectively. The average value of habluminallah behaviour in the range of values